Key Positions about the Economic Legacy of Aristotle - Borisonik, Hernan Gabriel (2016)
This article describes the main theses of some of the most celebrated authors that have explored the meaning of economy in Aristotle in Modern times. Firstly, the debate between the "modernist" and "primitivist" doctrines, which led to the subsequent discussion will be reviewed. Then, the ideas of Karl Marx, Joseph Schumpeter, Karl Polanyi and Moses Finley will be discussed. The object of this work is to show the interpretative debate and not to study Aristotelian economic ideas themselves.